Website Based Guestbook Design: Study At One of The Schools in Bandung - Oktavia, Oktavia; Rumaisha, Alya (Jurnal Computech & Bisnis (e-journal), 2024)
The research findings can be summarized as follows: Implementing this service information system facilitates the management of workshops for their managers, decreasing errors compared to the prior system. Including a booking service function allows consumers to expedite and streamline the service process, eliminating the need for an initial visit. Moreover, the system can provide more precise data due to storing each process in the database. Recommendations for enhancing the efficiency of the service information system include: Providing details about the daily service schedule is essential for the secretary to handle service appointments effectively. In addition, engaging employees in reporting their job outcomes enables the secretary to effectively oversee and provide vital monitoring data for the workshop owner.